GAME EDUKASI MENGENAL KEPULAUAN INDONESIA MENGGUNAKAN UNITY 3D UNTUK MENINGKATKAN MINAT BELAJAR SISWA SEKOLAH DASAR - Tri Aditama; Ade Irma Purnamasari; Tati Suprapti (Jurnal informasi dan komputer, 2022)
The very rapid development of technology, especially in learning educational games, has an impact in the world of education in utilizing educational games during the pandemic which reduces mobility in face-to-face learning in the pandemic era. The purpose of this research is to develop more modern and innovative learning media to increase interest in learning and make it easier to understand the Indonesian archipelago. And as an alternative learning media that is easy to understand and learn by elementary school students because in this modern era all of them have used effective learning methods such as educational games. To make games using Unity 3D 2019 software as game support software and the method used in this research is the Research and Development (R&D) research method to produce certain products and test their effectiveness, which can be useful for learning about the Indonesian archipelago for elementary school students. From the results of research data on educational games about the Indonesian archipelago, it can be seen that this educational game about the Indonesian archipelago gets an average score of 82.7% for the respondents in the very good category. Thus it can be said that educational games about the Indonesian archipelago can increase interest in learning in elementary school students.